Basic understanding of water flooding as a secondary recovery concept: Literature review - Martines, Gabriela; Prakoso, Suryo; Fathaddin, Muh. Taufiq; Rakhmanto, Pri Agung; Setiati, Rini; Mardiana, Dwi Atty (International research journal of engineering, IT and scientific research, 2022)
The need for energy and mineral resources is needed for the survival of human life. One of the results of minerals contained in the bowels of the earth is crude oil. Natural resources crude oil is still a top priority for natural resource needs in Indonesia. So it is necessary to explore and exploit crude oil resources. Secondary recovery (water flooding) and tertiary recovery methods are carried out on an oil and gas well to assist the process of producing oil to the surface. Water flooding is a method that is widely used because water is easy to obtain, water supply is quite cheap and mobility is low. Water injection is a second stage recovery method by injecting water into the reservoir so that the remaining oil can be pushed to the production well. Water flooding in its application can show a decreasing trend in production if the efficiency of this method in the reservoir has decreased, therefore after the water flooding recovery method has decreased production, the EOR method as a tertiary recovery method can be applied.